The Implementation of Character Education Based on 2013 Curriculum in the Elementary and Secondary Schools of Kupang Nusa Tenggara Timur Indonesia - ., Fahrurrozi; ., . (International Journal of Engineering and Technology, 2018)
This research aimed to know the implementation of character education based on the 2013 curriculum in Kupang City, Nusa Tenggara Timur. The research approach used to obtain the data was qualitative by using survey and descriptive designs. The research was conducted at SD and SMP in Kupang City of (1) SDN Osapa Kecil 2, (2) SD Inpres Osapa, (3) SDN Kelapa Lima 1, (4) SD 2 Don Bosco, ( 5) SD Don Bosco (6) SMPN 5 Kota Kupang, (7) SMPN 8 Kota Kupang. The data were collected using: (1) questionnaire, (2) document, (3) interview, and (4) observation. The research results indicated that the implementation of character education in Kupang City has been integrated as: (1) the teacher has implemented character education as stated in the lesson planning activities. (2) School culture in the effort to support the implementation of character education such as (a) discipline of school attendance, flag ceremony, school rules (b) religiously through greetings, smiles, congregational worship, (c) school programs through the socialization of character education either orally or in writing, (e) clean and healthy life in the form of cleanliness concern towards the school environment, (f) the studentsâ€™ culture of queuing up for any activity performance.Â Â
Keywords: Character Education; 2013 Curriculum; Elementary and Secondary Schools